Pneumonic versus Nonpneumonic Exacerbations of Chronic Obstructive Pulmonary Disease - Crisafulli, Ernesto; Manco, Alessandra; Ferrer, Miquel; Huerta, Arturo; Micheletto, Claudio; Girelli, Domenico; Clini, Enrico; Torres, Antoni (Seminars in Respiratory and Critical Care Medicine, 2020)
Patients with chronic obstructive pulmonary disease (COPD) often suffer acute exacerbations (AECOPD) and community-acquired pneumonia (CAP), named nonpneumonic and pneumonic exacerbations of COPD, respectively. Abnormal host defense mechanisms may play a role in the specificity of the systemic inflammatory response. Given the association of this aspect to some biomarkers at admission (e.g., C-reactive protein), it can be used to help to discriminate AECOPD and CAP, especially in cases with doubtful infiltrates and advanced lung impairment. Fever, sputum purulence, chills, and pleuritic pain are typical clinical features of CAP in a patient with COPD, whereas isolated dyspnea at admission has been reported to predict AECOPD. Although CAP may have a worse outcome in terms of mortality (in hospital and short term), length of hospitalization, and early readmission rates, this has only been confirmed in a few prospective studies. There is a lack of methodologically sound research confirming the impact of severe AECOPD and COPD + CAP. Here, we review studies reporting head-to-head comparisons between AECOPD and CAP + COPD in hospitalized patients. We focus on the epidemiology, risk factors, systemic inflammatory response, clinical and microbiological characteristics, outcomes, and treatment approaches. Finally, we briefly discuss some proposals on how we should orient research in the future.
Keywords: chronic obstructive pulmonary disease; acute exacerbation; community-acquired pneumonia; pneumonic; inflammatory response; outcomes